Entrance to a building on Winter Street, ca. 1890-1900 - Unknown (Tufts Archival Research Center, 2005)
Street-level view of the entrance to a building located on Winter Street near Tremont Street. Commercial products are displayed in the windows of the stores on either side of the main building included in the center of the photograph. Copyprint; designed by C.H. Blackall and G.F. Newton, ca. 1890-1900 9 1/8 x 6 15/16 Photographs